A taxonomic survey of intertidal soft corals (Coelenterata Octocorallia) in selected areas of Taklong Island, Nueva Valencia, Guimaras. - Denusta, Pastor Jones Tejero (1995.)
The study was conducted to make a taxonomic survey of intertidal soft corals in selected reef communities of Taklong Island, namely; Talisay, Balas Balabag, Calaparan, and Kaliruhan, and to make a dichotomous key of species found in the said communities. The line interest method was used to determine species composition. A total of 13 species belonging to ten genera of soft corals were represented in the said areas. Three species belong to the genus Sinularia, two to genus Lobophytum, and the rest belong to different genera (Sarcophyton sp., Nepthea sp., Pachyclavuria sp., Xenia., Clavuria sp., Malacacanthus sp., Capnella sp., and Asterospicularia sp.). Sarcophyton, Lobophytum, and Sinularia were the predominant species of soft corals in the said areas.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Corals, Soft -- Taklong Island; Coelenterata : Octocorallia